Pengaruh Strategi Pembelajaran dan Motivasi Belajar terhadap Prestasi Belajar Siswa pada Program Tahfidz Quran - Amalia Dwi Rahmah; Suwandi Suwandi (Edudeena: Journal of Islamic Religious Education)
Abstract: This study aims to verify whether this holds true for the Quran memorization (tahfidz) learning specifically at Al-Furqan Junior High School, Madrasatul Qur’an Tebuireng, Jombang. The research methodology employed a quantitative ex-post facto approach. Sampling was conducted using simple random sampling with 225 respondents. Questionnaires and documentation were the data collection techniques used in this research. Simple and multiple linear regressions were employed as the data analysis techniques. The research findings indicate that: (1) there is a partial influence between learning strategies and student motivation on Quran memorization achievement at Al-Furqan Junior High School, Madrasatul Quran Tebuireng, Jombang; (2) there is a simultaneous influence between learning strategies and motivation on Quran memorization achievement at Al-Furqan Junior High School, Madrasatul Quran Tebuireng, Jombang. This is evident in the selection of appropriate teaching strategies by teachers, fully supported by student motivation, which significantly improves students' memorization progress over time and enhances their learning achievements.